Efektivitas Panduan Pelatihan Konseling Kelompok Dengan Teknik Self Regulated Learning Untuk Meningkatkan Resiliensi Siswa Smp - Zada Avtana, Devana; Cahyaningrum, Vesti Dwi; Efendi, Moh Yusuf (Universitas Pakuan, 2025)
THE EFFECTIVENESS OF GROUP COUNSELING TRAINING GUIDE WITH SELF REGULATED LEARNING TECHNIQUES TO INCREASE THE RESILIENCE OF JUNIOR HIGH SCHOOL STUDENTSAcademic problems among students are not only related to cognitive abilities, but are also closely related to psychological aspects, particularly resilience. Students with low levels of resilience tend to exhibit academic symptoms such as easily giving up when faced with tasks, lacking confidence in expressing opinions, and struggling to control emotions. Resilience is an individual's ability to bounce back from adversity, adapt positively, and cope with life's challenges and pressures in a healthy and productive manner. The low level of resilience shown by junior high school students is a problem that needs to be addressed immediately. The purpose of this study was to test the effectiveness of group counseling training guidelines using self-regulated learning techniques to improve the resilience of students at SMPN 3 Bojonegoro. The method used was a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The analysis results indicate a significant improvement in students with low resilience, with 7 respondents showing an increase in average scores from 57% to 73% between the pretest and posttest. This suggests that group counseling training using self-regulated learning techniques is effective in enhancing students' resilience. This training program is expected to serve as a relevant and practical alternative service to help students optimize their resilience.